Kedudukan dan Peranan Kompilasi Hukum Islam dalam Sistem Hukum Nasion al - Barmawi Mukri (Fakultas Hukum Universitas Islam Indonesia, 2001)
The position on Isiamic law compilation based on Presidential Instmction number 1 the year of 1991 in National System ofLaw isdirected to the position of Presidential Instniction it self in the procedure on ordinance In Indonesia, itmeans that Islamic Law Compilation is subordinate or it is lower than ordinance and Governmental Regulation. There no forbidden for Religious Judge however to make islamic Law Compilation Is one ofthereference ofguldence in deciding caseat Religious Court, especially ifitis fail to gain the basic material on the higherrule oflegislation.